Food allergy in the World Health Organization's International Classification of Diseases (ICD)‐11. Issue 11 (16th November 2022) - Tanno, Luciana Kase; Demoly, Pascal
Abstract: There are increasing global data regarding the prevalence of food allergy and food‐induced anaphylaxis. However, knowledge in morbidity and mortality epidemiological data is still not optimal, and international comparable standards remain poorly accessed. This information could in turn support better clinical practice and possibly prevent future severe reactions and avoidable fatalities. The International Classification of Diseases (ICD) is the standard diagnostic tool used for epidemiology, health management, and clinical purposes supported by the World Health Organization (WHO). It is also used to determine health care payment and reimbursement of providers and health care services in hospitals. Thanks to the academic and technical efforts under the ALLERGY in ICD‐11 initiative the pioneer "Allergy and hypersensitivity conditions" section has been built under the "Disorders of the Immune System" chapter of the ICD‐11. The "Food hypersensitivity" (FH) subsection is classified under the "Complex allergic or hypersensitivity conditions" section and "Food‐induced anaphylaxis" is under the "Anaphylaxis" section. In order to inform the development of strategies to reduce preventable FHs/food allergies, the burden of disease in different healthcare settings and patient populations and their common etiologies need to be understood. Besides, greater specificity regarding clinical conditions and services delivered will provide payers, policy makers, and providers with better information to make major refinements to countries payment and reimbursement systems, including the design and implementation of pay‐for‐performance program.The new classification addressed to FHs will enable the collection of more accurate epidemiological data to support quality management of patients with FHs/food allergies, and better facilitate health care planning and decision‐making and public health measures to prevent and reduce their morbidity and mortality. The improved logic and standardized definitions through the ICD‐11 (and other WHO classifications) will also facilitate international comparisons of quality care and the sharing of best practice globally.